Valorisation of natural extracts from marine source focused on marine by-products: A review - Ferraro, Vincenza; Cruz, Isabel B.; Jorge, Ruben Ferreira; Malcata, F. Xavier; Pintado, Manuela E.; Castro, Paula M.L. (Food research international, 2010)
The wide chemical and biological diversity observed in the marine environment makes the ocean an extraordinary source of high added value compounds (HAVC) which can be employed in many applications. Minerals, lipids, amino acids, polysaccharides and proteins from marine sources have unique features and, surprisingly, their highest concentration is often found in parts of marine organisms that are commonly discarded. Fish heads, viscera, skin, tails, offal and blood, as well as seafood shells possess several HAVC suitable for human health applications, yet most end up as residues throughout the raw material processing. This review updates information on this issue and conveys critical analysis of the chief methodologies to carry out extraction, purification and eventual transformation, with a focus on their actual and potential applications.